Pengaruh Akuntabilitas dan Transparansi Pelaporan Terhadap Digitalisasi Pengelolaan Keuangan Desa di Era Smart Village: Studi Kasus di Kecamatan Tolinggula - Dwi Prastiani Ibrahim; Sahmin Noholo; Siti Pratiwi Husain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of accountability and reporting transparency on the digitalization of village financial management in the Smart Village era in villages located in Tolinggula District, North Gorontalo Regency. This research employed a quantitative method with a verificative approach and causal research design. Data were collected through questionnaires distributed to village officials involved in village financial management. The data were analyzed using multiple linear regression analysis to determine the partial and simultaneous effects of the independent variables on the dependent variable. The results indicate that accountability does not have a significant effect on the digitalization of village financial management. This condition occurs because the implementation of accountability is still administrative and manual, so it has not been fully integrated into digital systems. Meanwhile, reporting transparency has a positive and significant effect on the digitalization of village financial management. The higher the level of reporting transparency, the higher the implementation of digitalization in village financial management. Simultaneously, accountability and reporting transparency significantly affect the digitalization of village financial management in the Smart Village era. This study concludes that the digitalization of village financial management is more strongly influenced by reporting transparency than accountability. Therefore, strengthening digital system integration, improving human resource competencies, and developing information technology infrastructure are necessary to support the realization of effective, transparent, accountable, and Smart Village-based village governance.